2013
DOI: 10.1038/sj.bdj.2013.432
|View full text |Cite
|
Sign up to set email alerts
|

Future prospects of systemic host modulatory agents in periodontal therapy

Abstract: Periodontitis is an inflammatory disease caused by microbial infection that leads to destruction of supporting tissues of the teeth. The periodontal tissue destruction is a result of both microbial activity as well as host response. The best chance for clinical improvement may come from implementing complementary treatment strategies that target different aspects of the periodontal balance. Host response modulation, in combination with conventional treatment, offers to restore the balance between health and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
(35 reference statements)
0
15
0
2
Order By: Relevance
“…Current therapies for periodontal disease involve mechanical and surgical procedures that do not allow for the recovery of lost tissue. Drugs used and tested to treat osteoporosis, such as bisphosphonates , statins , β‐blockers and anti‐receptor activator of nuclear factor kappa‐B ligand and sclerostin antibodies , as well as anabolic agents such as parathyroid hormone have been studied in periodontal disease with good results. Previous studies showed that LP533401 was effective in preventing systemic bone loss, and enhanced bone mass in mice and rats .…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies for periodontal disease involve mechanical and surgical procedures that do not allow for the recovery of lost tissue. Drugs used and tested to treat osteoporosis, such as bisphosphonates , statins , β‐blockers and anti‐receptor activator of nuclear factor kappa‐B ligand and sclerostin antibodies , as well as anabolic agents such as parathyroid hormone have been studied in periodontal disease with good results. Previous studies showed that LP533401 was effective in preventing systemic bone loss, and enhanced bone mass in mice and rats .…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclast activation is central in the pathogenesis of periodontitis 3739 . Pharmacologic inhibitors of osteoclast function or differentiation attenuate bone loss in animal models of periodontitis and have been entertained as potential interventions for periodontal disease 4045 . Systemic hormones and inflammatory cytokines play key role in osteoclast formation and activation 38, 43, 46, 47 .…”
Section: Discussionmentioning
confidence: 99%
“…*P <0.05; † P <0.01. disease. [40][41][42][43][44][45] Systemic hormones and inflammatory cytokines play key roles in osteoclast formation and activation. 38,43,46,47 Indeed, association of systemic diseases that show increased osteoclast activity with periodontal bone loss has been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical parameters are still considered the gold‐standard outcomes when monitoring the results from any periodontal therapy. However, in search of a better understanding of periodontal diseases, microbiologic 5 and host‐related 6 aspects also have been studied. Nitrite is among them (Fig.…”
mentioning
confidence: 99%